Allele frequency of SLC4A3 (PRA1), TTC8 (PRA2), and PRA-prcd mutations in golden retrievers in Brazil - Trecenti-Santana, Anelize Souza; Guiraldelli, Giulia Gumiero; Albertino, Lukas Garrido; Ferreira, Julia Franco; Andrade, Fabiana Michelsen; Borges, Alexandre Secorun; Oliveira-Filho, José Paes (Frontiers in Veterinary Science, 2022)
Progressive retinal atrophy (PRA) is a term used in veterinary medicine to describe inherited and progressive retinal diseases characterized by progressive retinal degeneration and loss of vision. In the Golden Retriever (GR) breed, the mutations associated with PRA have an autosomal recessive inheritance pattern. This study aimed to verify the allele frequency of PRA1, PRA2, and PRA-prcd in the GR breed in Brazil. A total of 121 GR DNA samples (n= 66 females and n= 55 males) were analysed. All animals assessed in this study were identified as wild-type (121/121 animals; 100%) for PRA1 and PRA2 mutations; therefore, no carrier or homozygous animals were identified in this population. For the PRA-prcd mutation, 118 animals (118/121 animals; 97.52%) were wild-type. Three animals were genotyped as heterozygous for PRA-prcd (3/121 animals; 2.47%; p= 1.23%), demonstrating that this mutation is still present in some bloodlines and animals in Brazil, even with a rare prevalence. In addition, the vast majority (98.3%) of Brazilian breeders assessed in this study were unaware of these mutations as a cause of blindness in the Golden Retriever.